Eco-friendly degreasing adsorbent derived from oily scum and walnut shells for oilfield sewage treatment and industrial oils adsorption - Chao Tang; Jiaojiao Guan; Yuliang Lin (PLoS ONE, 2025)
Oily scum (OS) and walnut shells (WS) were employed to produce an eco-friendly degreasing adsorbent (DA) for the treatment of oilfield sewage and the adsorption of industrial oils. The optimal conditions for preparing DA were established as follows: a mass ratio of OS to WS of 1:2, a pyrolysis temperature of 600°C, a heating rate of 10°C/min, and a pyrolysis duration of 2 hours. The carbon mass fraction in DA was determined to be 90.72%, with a BET specific surface area of 563.31 m2/g, a pore volume of 0.794 cm3/g, and an average pore size of 5.618 nm. The pores were predominantly mesoporous, centered around a size of 3 nm. In oilfield sewage treatment tests, DA achieved a remarkable reduction of 92.64% in the petroleum content of oilfield sewage, outperforming activated carbon (AC) treatment by 13.52% under identical conditions. In tests for industrial oil adsorption, DA demonstrated initial adsorption rates of 138.55 mg/(g·min) for diesel and 189.52 mg/(g·min) for crude oil, achieving cumulative adsorption capacities of 973.3 mg/g and 1017 mg/g for diesel and crude oil, respectively. Thermal regeneration of DA significantly enhanced its oil affinity, markedly improving its initial adsorption rates. Furthermore, the cumulative adsorption capacity of regenerated DA for diesel and crude oil reached 966.88 mg/g and 946.15 mg/g respectively, surpassing that of regenerated AC for diesel (585.47 mg/g) and crude oil (849.21 mg/g). Additionally, DA showed a shorter penetration adsorption time, positioning it as a feasible option for recycling and as an eco-friendly emergency adsorbent in the context of industrial oil spills.